Advanced applications of sustainable and biological nano-polymers in agricultural production - Vinzant, Kari; Rashid, Mohammad; Khodakovskaya, Mariya V. (Frontiers in Plant Science, 2023)
It is no doubt that on a global scale our agricultural systems will need to become more perfect, efficient systems in the near future. Though still in its infancy, nanotechnology has been one proposed means of improving agriculture; nanoparticles (NP) offer the potential solution to depleted and dry soils, a method for the controlled release of agrochemicals, and a potentially easier means of gene editing in plants. However, with this potential comes concern: NP applied in soils may end up in watersheds and groundwater, or NP applied to food crops may carry into the end product, and potentially end up in our food supply. These are valid points that are not likely to be fully answered in the immediate future due to the complexity of soil-NP interactions and other confounding variables. Due to these unanswered concerns, it is obviously preferred that NP in early agricultural applications be biodegradable, low in toxicity, and ideally cheap and sustainable to manufacture. Thankfully, there are many different biologically derived, cost-efficient, and non-toxic polymers that may be suitable for agriculture. In this mini-review, we discuss some promising organic nanomaterials and their potential use for the optimization and enhancement of agricultural practices.